An interpretation of the Hubble expansion by the antigraviton-graviton theory - WONG, Wing-hong; WONG, Wing-to; WONG, Wing-keung; WONG, Ling-mei (International Journal of Advanced Astronomy, 2014)
Building on the foundation of the antigraviton-graviton theory (AGT), which was published recently, in this paper, we shall give a theoretical interpretation of the Hubble expansion of the universe, without adopting the dark matter hypothesis nor the dark energy hypothesis. Our theoretical results may be summarized by two points. Firstly, in contrast to Einstein’s general relativity theory (GRT), our AGT predicts that the universe will be expanding, provided that its average density is positive definite. Secondly, our AGT has found that the universe may be divided into two spatial regions. Defining the radius ratio as the ratio of the radius to the radius of the visible universe, it is found that when the radius ratio is less than 0.125, the expansion of the universe can be nearly exactly described by the Hubble formula. When the radius ratio is between 0.125 and 0.64, the expansion rate is greater than that given by the Hubble formula. And the theoretical Hubble expansion rate reaches its maximum when the radius ratio is at about 0.64. Keywords: Cosmology: Theory, Dark Energy, Dark Matter, Galaxies: Kinematics and Dynamics, Gravitation, Large-Scale Structure of Universe.